GRANULOCYTES DIFFERENTIAL OF BALI CATTLE IN THE DIFFERENT HIGHER AT NUSA PENIDA - Adnyani, Ni Made Riska; Suwiti, Ni Ketut; Setiasih, Ni Luh Eka (Buletin Veteriner Udayana, 2018)
The aim of this study is to determine the differential granulocytes performed on neutrophils, eosinophils, and basophils in bali cattle which are raised in the highlands and lowlands in Nusa Penida. Blood samples were taken from 60 female bali cattle. Bali cattle blood sample was done randomly using multi-stage sampling. Blood collection was done through a jugular vein using a venoject. Blood smear was done using slide technique immediately, followed by fixation and sample staining using Giemsa. Differential leucocytes were counted using battlement method until 100 cells was found using 1000x magnification. Completely randomized design (CRD) was used for data analysis. The obtained data were analyzed with Independent Samples T-Test. The results showed that a type of maintenance location (highlands and lowlands) had a significant effect on neutrophil, but has not significant effect to eosinophils and basophils. The percentage of bali cattle neutrophils in the highlands is lower than in the lowlands.